2013
DOI: 10.1002/job.1860
|View full text |Cite
|
Sign up to set email alerts
|

Workplace racial/ethnic similarity, job satisfaction, and lumbar back health among warehouse workers: Asymmetric reactions across racial/ethnic groups

Abstract: Summary Racial and ethnic minority employees constitute a significant proportion of the U.S. workforce. The literature on demographic similarity in the workplace suggests that the proportion of co‐workers who share the same racial/ethnic background (racial/ethnic similarity) can influence job attitudes and employee well‐being and that the reactions to racial/ethnic similarity may differ between the racially dominant and subordinate groups. This study applies status construction theory to examine the extent to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 112 publications
1
24
0
Order By: Relevance
“…Enchautegui- de-Jesús et al (2006) analyze a sample of Black and Latinx workers in New York City and Chicago and find that psychological well-being is lowest among workers in token jobs and improves with the proportion of same-race coworkers, but begins to decline slightly at the highest levels of proportional representation (inverse J-shaped). Finally, Hoppe et al (2014) examine the effect of workplace racial similarity on lumbar back health among warehouse workers. They find a positive relationship between racial/ethnic similarity and back health among Black workers.…”
Section: Relational Demography Tokenism and Compositionmentioning
confidence: 99%
See 2 more Smart Citations
“…Enchautegui- de-Jesús et al (2006) analyze a sample of Black and Latinx workers in New York City and Chicago and find that psychological well-being is lowest among workers in token jobs and improves with the proportion of same-race coworkers, but begins to decline slightly at the highest levels of proportional representation (inverse J-shaped). Finally, Hoppe et al (2014) examine the effect of workplace racial similarity on lumbar back health among warehouse workers. They find a positive relationship between racial/ethnic similarity and back health among Black workers.…”
Section: Relational Demography Tokenism and Compositionmentioning
confidence: 99%
“…From the stress process health perspective, and consistent with the MCB literature, supportive workplace relationships, as a key resource, are presumed to offset stressful circumstances and therefore positively affect psychological well-being. Of the three studies to examine racial composition and well-being, only Hoppe et al (2014) incorporated a measure of social support. They find that greater coworker social support is associated with better lumbar back health.…”
Section: Workplace Social Relations: Management Citizen Behavior and mentioning
confidence: 99%
See 1 more Smart Citation
“…Workplace environment includes several characteristics such as ethnic climate, leadership, safety climate, competition level, facility infrastructure, workplace interaction, and trade type (e.g. mining, manufacturing, warehousing) (Hoppe, Fujishiro, & Heaney, 2014). Workplace features such as safety climate (Probst et al, 2008), trade (Baradan & Usmen, 2006), leadership (Vries, Koster, & Stam, 2016), and ethnic climate (Hoppe et al, 2014) have been shown to influence injury risk in workplaces.…”
Section: Decision Framework For Injury Riskmentioning
confidence: 99%
“…mining, manufacturing, warehousing) (Hoppe, Fujishiro, & Heaney, 2014). Workplace features such as safety climate (Probst et al, 2008), trade (Baradan & Usmen, 2006), leadership (Vries, Koster, & Stam, 2016), and ethnic climate (Hoppe et al, 2014) have been shown to influence injury risk in workplaces. Task-related characteristics include factors such as ergonomic design, task characteristics (e.g., hazard level, cognitive complexity, physical effort), task exposure, equipment quality, IS technology design factors (e.g., interface design, usability features), multitasking, loading factors, mental overload, task response, information sharing, handoff (e.g., shift change), number of transfers, etc.…”
Section: Decision Framework For Injury Riskmentioning
confidence: 99%